2004
DOI: 10.2169/internalmedicine.43.571
|View full text |Cite
|
Sign up to set email alerts
|

Adult-onset Idiopathic Hypogonadotropic Hypogonadism due to Isolated Pituitary Gonadotropin Deficiency

Abstract: A 25-year-old Japanese man with adult-onset idiopathic hypogonadotropic hypogonadism is reported. He had been delivered normally, had normal puberty, and experienced erectile dysfunction at age 24 years. Brain MRI revealed no abnormal findings and endocrinological data supported the diagnosis of isolated gonadotropin deficiency. Although most patients with idiopathic hypogonadotropic hypogonadism have a hypothalamic dysfunction, the lesion in this case may be considered to be in the pituitary since repetitive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 15 publications
(15 reference statements)
0
2
0
Order By: Relevance
“…Most clinical studies have found that administration of pulsive GnRH therapy can restore gonadotropin secretion and spermatogenesis, suggesting that GnRH neurons in the hypothalamus were impaired [3,10]. However, recent evidence from two cases determined that pituitary gonadotrophs were impaired because no increase of gonadotropins was evoked by pulsive GnRH stimulation [9,11]. As for our patients, the extremely low levels of gonadotropins and testosterone, which could not be stimulated by GnRHa, indicate severe and specifically damaged pituitary gonadotrophs.…”
Section: Dear Editormentioning
confidence: 53%
See 1 more Smart Citation
“…Most clinical studies have found that administration of pulsive GnRH therapy can restore gonadotropin secretion and spermatogenesis, suggesting that GnRH neurons in the hypothalamus were impaired [3,10]. However, recent evidence from two cases determined that pituitary gonadotrophs were impaired because no increase of gonadotropins was evoked by pulsive GnRH stimulation [9,11]. As for our patients, the extremely low levels of gonadotropins and testosterone, which could not be stimulated by GnRHa, indicate severe and specifically damaged pituitary gonadotrophs.…”
Section: Dear Editormentioning
confidence: 53%
“…Since then, only 10 more cases have been reported [9], including two patients from Japan [10,11]. The underlying mechanism has not yet been elucidated because of the rarity of this disease and lack of pathological and immunohistochemical information from hypothalamic or pituitary tissues.…”
Section: Dear Editormentioning
confidence: 99%